2023
DOI: 10.1007/s12325-023-02521-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of Kukoamine B in Healthy Volunteers: A Randomized, Double-Blind, Placebo-Controlled, Multiple-Dose Phase I Study

Abstract: Introduction: Kukoamine B (KB) is a novel sepsis therapeutic drug targeting lipopolysaccharide and CpG DNA. This study aims to evaluate the safety, tolerability, and pharmacokinetic (PK) profile of multiple doses of KB in healthy volunteers. Methods: Healthy volunteers were randomized at a 1:1:1:1 ratio to receive multiple intravenous infusion doses of KB 0.06 mg/kg, 0.12 mg/kg,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Wang et al [ 80 ] used an exposure-response model to optimize dose selection in phase IIb clinical trials and recommended a 0.24 mg/kg regimen. A randomized, double-masked, placebo-controlled, multi-dose phase I study also demonstrated that single and multiple intravenous infusions of 0.06–0.24 mg/kg were safe and tolerable in healthy volunteers [ 81 ].…”
Section: Alkaloid Compoundsmentioning
confidence: 99%
“…Wang et al [ 80 ] used an exposure-response model to optimize dose selection in phase IIb clinical trials and recommended a 0.24 mg/kg regimen. A randomized, double-masked, placebo-controlled, multi-dose phase I study also demonstrated that single and multiple intravenous infusions of 0.06–0.24 mg/kg were safe and tolerable in healthy volunteers [ 81 ].…”
Section: Alkaloid Compoundsmentioning
confidence: 99%